2012
DOI: 10.1029/2012tc003112
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary morphotectonic mapping of the Wadi Araba and implications for the tectonic activity of the southern Dead Sea fault

Abstract: [1] The Dead Sea strike-slip fault accommodates the northward motion of Arabia relative to Sinai at a rate of $5 mm/yr. The southern segment of the fault, the Wadi Araba fault, runs along a valley blanketed in Quaternary sediments. We first focused on understanding the relative and absolute timing of emplacement of the alluvial surfaces. We then determined the probable source of the sediments before assessing their lateral offset to constrain the late Pleistocene fault slip rate. Seven successive morphostratig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 88 publications
(109 reference statements)
3
42
0
Order By: Relevance
“…Regional and local slip rates on various segments of DST system have been measured by several methods. Quaternary slip rates in the range of 2 to 8 mm/yr were estimated based on offset surface features along segments of the Arava and EvronaF [ Zak and Freund , ; Garfunkel , ; Ginat et al ., ; Klinger et al ., , ; Niemi et al ., ; Makovsky et al ., ; Le Béon et al ., , ]. Geodetic estimates of the current horizontal plate motion across the DST are in the range of 3.7 to 7.5 mm/yr [ Wdowinski et al ., 2004; Mahmoud et al ., 2005; Ostrovsky , 2005; Gomez et al ., ; Le Béon et al ., ; Al Tarazi et al ., ; Sadeh et al ., ] and are in agreement with the geological rates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regional and local slip rates on various segments of DST system have been measured by several methods. Quaternary slip rates in the range of 2 to 8 mm/yr were estimated based on offset surface features along segments of the Arava and EvronaF [ Zak and Freund , ; Garfunkel , ; Ginat et al ., ; Klinger et al ., , ; Niemi et al ., ; Makovsky et al ., ; Le Béon et al ., , ]. Geodetic estimates of the current horizontal plate motion across the DST are in the range of 3.7 to 7.5 mm/yr [ Wdowinski et al ., 2004; Mahmoud et al ., 2005; Ostrovsky , 2005; Gomez et al ., ; Le Béon et al ., ; Al Tarazi et al ., ; Sadeh et al ., ] and are in agreement with the geological rates.…”
Section: Discussionsupporting
confidence: 87%
“…North of the GEA, the DST passes along the Arava (Wadi 'Arabah) Valley. Mapping of offset surface features, aided by field observations, aerial photo analysis, and paleoseismic trenches [e.g., Zak and Freund , ; Garfunkel et al ., ; Ginat et al ., ; Klinger et al ., , ; Niemi et al ., ; Le Béon et al ., , ] and recent gravimetric and magnetic studies [ Haberland et al ., ; ten Brink et al ., ] revealed that the DST traverses the central Arava Valley predominantly as a single, almost continuous, sinistral strike‐slip fault. Modeling of gravity and magnetic data [ ten Brink et al ., , ], and seismic profiles [ Frieslander , ] revealed separate longitudinal basins along the Arava Valley.…”
Section: Previous Workmentioning
confidence: 99%
“…From a regional perspective, the extensive measurements presently available imply that the average slip rate of the main part of the Haiyuan fault is 7.0 ± 2.0 mm/year, with no evidence of Latest Quaternary secular variation (Figure a). Other studies have documented consistent slip rates over multiple time scales, as we have here (Blisniuk et al, ; Cowgill et al, ; Gold et al, ; Grove & Niemi, ; Le Beon et al, , ; Toké et al, ). In terms of lateral variation, excluding earlier studies of Zhang et al (), He et al (), and Yuan et al (), which lacked rigorous geochronological constraints, the horizontal slip rate along the Haiyuan fault appears to slightly decrease eastward from Jinqiang He section to that broken in the 1920 Haiyuan earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…CRN dating is nowadays commonly used to infer the ages of alluvial terraces from surface and subsurface samples in a wide range of tectonic and climatic contexts (e.g., Anderson et al, ; Balco et al, ; Delmas et al, ; Gold et al, ; Gosse & Phillips, ; Guilbaud et al, ; Hancock et al, ; Hetzel, ; Lal, ; Le Béon et al, , ; Meriaux et al, ; Perrineau et al, ; Repka et al, ; Saint‐Carlier et al, ; Van der Woerd et al, , ; Yang et al, ; Yang et al, ). At Site S1, we collected quartz‐rich pebbles and cobbles from the terrace surfaces and amalgamated quartz‐rich gravel samples along depth profiles in 2‐ to 3‐m‐deep pits dug within the terraces to measure the concentration of 10 Be and 26 Al.…”
Section: Methodsologymentioning
confidence: 99%